2020
DOI: 10.1536/ihj.19-277
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Circulating Neuregulin-1 and Coronary Collateral Circulation in Patients with Coronary Artery Disease

Abstract: Coronary collateral circulation (CCC) plays a crucial role in myocardial blood supply, especially for ischemic myocardium. Previous study has shown that neuregulin-1 is a prominent angiogenic factor in diabetic cardiomyopathy, whereas the relationship between neuregulin-1 and CCC has not been investigated. Thus, we aimed to investigate relationship between circulating neuregulin-1 levels and CCC in stable coronary artery disease patients. Coronary artery disease patients with a stenosis of !90% as evidenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…Продемонстрировано его непосредственное влияние на кардиомиоциты, эндотелиальные клетки, макрофаги и фибробласты, приводящее к активной пролиферации клеток, антиапоптозу, противовоспалительному и антиоксидантному эффектам, а также регулирующей роли в процессах энергетического метаболизма миокарда [1][2][3][4]. При этом работы по изучению роли NRG-1 у пациентов с ишемической болезнью сердца (ИБС) крайне малочисленны [5,6], а данные, полученные авторами, весьма противоречивы, в связи с чем представляется актуальным изучение концентрации NRG-1 у пациентов с различной выраженностью атеросклеротического поражения коронарных артерий (КА), в т.ч. в рамках их клинико-инструментальных особенностей.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Продемонстрировано его непосредственное влияние на кардиомиоциты, эндотелиальные клетки, макрофаги и фибробласты, приводящее к активной пролиферации клеток, антиапоптозу, противовоспалительному и антиоксидантному эффектам, а также регулирующей роли в процессах энергетического метаболизма миокарда [1][2][3][4]. При этом работы по изучению роли NRG-1 у пациентов с ишемической болезнью сердца (ИБС) крайне малочисленны [5,6], а данные, полученные авторами, весьма противоречивы, в связи с чем представляется актуальным изучение концентрации NRG-1 у пациентов с различной выраженностью атеросклеротического поражения коронарных артерий (КА), в т.ч. в рамках их клинико-инструментальных особенностей.…”
Section: Discussionunclassified
“…Примечание: NRG-1 -нейрегулин-1, SYNTAX -Synergy between Percutaneous Coronary Intervention with TAXUS and Cardiac Surgery. 2020), в которых было показано, что концентрации NRG-1 и NRG-4 в плазме крови отрицательно коррелировали с тяжестью ИБС и развитием коллатерального кровотока, а также оказались надежными независимыми предикторами хорошего его развития [6,8]. Rahimzadeh M, et al (2020) продемонстрирована связь NRG-4 с низким риском развития острого коронарного синдрома [9].…”
Section: Discussionunclassified
“…A recent study demonstrated the positive correlation between circulating NRG-1 and left ventricular ejection fraction [72], supporting the idea that NRG-1 is contributing to compensatory cardiac responses. The levels of both NRG-1 and NRG-4 correlate inversely with the severity of coronary artery disease (CAD) [27,70] and coronary collateral circulation [73]. The potential explanation may include the reduction in the synthesis or secretion of NRG-1 and NRG-4 by endothelial cells [74,75] associated with endothelial dysfunction in CAD [76,77].…”
Section: Circulating Neuregulin Levelsmentioning
confidence: 99%
“…Oxidative stress and inflammation play a significant role in the atherosclerosis process of CAD. A previous study has shown that neuregulin-1 is a prominent angiogenic factor in diabetic cardiomyopathy, whereas the relationship between neuregulin-1 and MDA plasma level has not been investigated [3]. The malondialdehyde (MDA) was produced during oxidative stress on lipid peroxidation [2].…”
Section: Introductionmentioning
confidence: 99%